Dissent on the Margins : How Soviet Jehovah's Witnesses Defied Communism and Lived to Preach About It - Baran, Emily B. (New York Oxford University Press, 2014)
Emily B. Baran offers a gripping history of how a small, American-based religious community, the Jehovah's Witnesses, found its way into the Soviet Union after World War II, survived decades of brutal persecution, and emerged as one of the region's fastest growing religions after the Soviet Union's collapse in 1991. In telling the story of this often misunderstood faith, Baran explores the shifting boundaries of religious dissent, non-conformity, and human rights in the Soviet Union and its successor states. Soviet Jehovah's Witnesses are a fascinating case study of dissent beyond urban, intellectual nonconformists. Witnesses, who were generally rural, poorly educated, and utterly marginalized from society, resisted state pressure to conform. They instead constructed alternative communities based on adherence to religious principles established by the Witnesses' international center in Brooklyn, New York. The Soviet state considered Witnesses to be the most reactionary of all underground religious movements, and used extraordinary measures to try to eliminate this threat. Yet Witnesses survived, while the Soviet system did not
Include Map, Notes and Index
Keywords: Soviet Union -- Russia (Federation) -- Christianity and atheism